Bounded solutions of differential equations with “slow” time - Sotnichenko, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The problem of existence of bounded solutions on the whole number line of a nonlinear system of first order with “slow” time is studied.